Outcomes of manual small incision cataract surgery (mSICS) compared with phacoemulsification from population based outreach eye camp, in Yogyakarta and Southern Central Java Region, Indonesia - Indra Tri Mahayana; Reny Setyowati; Tri Winarti; Suhardjo Prawiroranu (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2018)
In this study, we compared the effectiveness (comparison of post-operative visual acuity/VA) of phacoemulsification by ophthalmologists versus manual small incision cataract surgery (mSICS) by residents in a mass cataract surgery setting. This research was a cross-sectional study of 1137 cataract patients who underwent cataract surgery by ophthalmologists and residents in outreach eye camps during 2015-2017 (3 years). There were 554 patients who underwent phacoemulsification by ophthalmologists and 583 patients who underwent mSICS by residents. Basic patient characteristics data, such as: age, sex and pre-surgical VA were recorded and we compared pre- versus post-operative VA (best corrected VA/BCVA) and surgical adverse events in 4 weeks post-operative follow-up. In basic subject characteristics, there were no differences in age and sex between the 2 groups, in which 602 (52.9%) were men and 535 (47.1%) were women. Overall 583 (51.3%) eyes received mSICS and 554 (48,7%) eyes received phacoemulsification. Visual acuity improvement (≥6/18) was achieved in 59.61% of eyes after phacoemulsification and 53.5% eyes after mSICS. There were no statistical differences in visual outcome results between both groups (p=0.10). Severe surgical adverse events (nucleus drop and endophthalmitis) were found in 3 cases (0.26%) and choroidal bleeding in 1 eye (0.08%). The effectiveness of phacoemulsification and mSICS in improving visual acuity was found similar between ophthalmologists and residents. mSICS should be considered for more frequent use in high volume mass cataract surgery.KEYWORDS cataract surgery; phacoemulsification; manual small incision cataract surgery; outreach program; community ophthalmology